Alkali Assisted Reduction of Open‐Circuit Voltage Deficit in CZTSe Solar Cells. Issue 10 (4th September 2017) - Garud, Siddhartha; Vermang, Bart; Sahayaraj, Sylvester; Ranjbar, Samaneh; Brammertz, Guy; Meuris, Marc; Smets, Arno; Poortmans, Jef
Abstract : Pure selenide Cu2 ZnSnSe4 solar cells were fabricated with a maximum achieved open‐circuit voltage ( V OC ) of 454 mV, which is on par with the highest known V OC for this technology (Bourdais et al., Adv. Energ. Mater .2016, 6 ). A simple, non‐vacuum, spin coating technique was developed for the introduction of alkali ions (Li +, K +, Rb + ) before two annealing steps. The presence of Rb and Li ions in particular, was observed to reduce recombination in the bulk and increase minority charge carrier decay time. This resulted in the reduction of the redshift in the photoluminescence peak from the bandgap and the V OC deficit. Bandgap variations and electrostatic potential fluctuations in conduction and valence bands were investigated as aspects likely affected by alkali ions. Abstract : Pure selenide Cu2 ZnSnSe4 solar cells were fabricated with a maximum achieved open‐circuit voltage (VOC) of 454 mV. A simple, non‐vacuum, spin coating technique was developed for the introduction of alkali ions (Li +, K +, Rb + ) in the absorber for this purpose.